(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today Wireless network technology are widely used technology in many organizations. Wireless LANs transmit and receive data without physical channel means over the air so no need for a wired connection. For this radio frequency (RF) technology is used. Without any cables attached, a wireless network allows devices to remain linked to the network. The main advantage of wireless network is that it is typically cheaper, simpler, quicker to set up as wireless network does not require expensive wiring. Mainly radio communication is used to implement wireless communication networks. At physical level of OSI model network structure this implementation takes place. Examples of wireless networks include cell phone networks, Wi-Fi local networks & terrestrial microwave networks. The advent of wireless sensor network has given birth to new kinds of routing algorithms and new security threats.